2008
DOI: 10.1255/ejms.936
|View full text |Cite
|
Sign up to set email alerts
|

Internal Energy Effects on the Ion/Molecule Reactions of Ionized Methyl Isocyanide

Abstract: Electron ionization of methyl isocyanide in various chemical ionization conditions is reported and, depending on the energy conditions used, different ion/molecule reactions are observed. It is proposed, on the basis of combined quantum chemical (DFT) calculations and tandem mass spectrometric experiments, that a common intermediate could be a cumulenic ionized dimer dissociating in the ion source following two energy depending competitive channels, a loss of a hydrogen atom and a loss of a methyl group. Propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…Beside these thorough but limited studies, a need for the finding of other examples of cationic nucleophilic aromatic substitution reactions is consequently evident in order to have a more general picture of this type of reaction and to provide new insight into its mechanism. In this context, we have recently shown that, in the gas phase, methyl isocyanide, CH 3 NC, is an efficient nucleophilic reagent. This is the result of its high ionization energy (11.24 eV) and its relatively low proton affinity (839 kJ/mol) which prevents charge and proton exchange processes. Moreover, the high dipole moment of CH 3 NC (3.85 D) favors its association with charged species and consequently increases its reaction efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside these thorough but limited studies, a need for the finding of other examples of cationic nucleophilic aromatic substitution reactions is consequently evident in order to have a more general picture of this type of reaction and to provide new insight into its mechanism. In this context, we have recently shown that, in the gas phase, methyl isocyanide, CH 3 NC, is an efficient nucleophilic reagent. This is the result of its high ionization energy (11.24 eV) and its relatively low proton affinity (839 kJ/mol) which prevents charge and proton exchange processes. Moreover, the high dipole moment of CH 3 NC (3.85 D) favors its association with charged species and consequently increases its reaction efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we have recently shown that, in the gas phase, methyl isocyanide, CH 3 NC, is an efficient nucleophilic reagent. [15][16][17][18] This is the result of its high ionization energy (11.24 eV) and its relatively low proton affinity (839 kJ/mol) 19 which prevents charge and proton exchange processes. Moreover, the high dipole moment of CH 3 NC (3.85 D) favors its association with charged species and consequently increases its reaction efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Sector instruments can also be used for IMR studies as shown by Gerbaux and co-workers. They made use of a six-sector instrument with the geometry of cE 1 B 1 cE 2 ccE 3 B 2 cE 4 (where E stands for an electric sector, B stands for a magnetic sector, and c stands for collision cell). The first three sectors are used to select the beam of ions and slow them down before they enter the hexapole cell. By slowing the ions down, it allows for the interaction with the neutrals to be maximized.…”
Section: Instrumentationmentioning
confidence: 99%
“…Beside these thorough but limited studies, a need for the finding of other examples of nucleophilic aromatic substitution reactions is consequently evident in order to have a more general picture of this type of reaction and to provide new insight into its mechanism. In this context, we have recently shown that, in the gas phase, methyl isocyanide, CH 3 NC, is an efficient nucleophilic reagent toward cationic substrates. This is the result of its high ionization energy (11.24 eV) and its relatively low proton affinity (839 kJ mol −1 ), which prevent charge and proton exchange processes, respectively. Moreover, the high dipole moment of CH 3 NC (3.85 D) favors its association with charged species and consequently increases its reaction efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we have recently shown that, in the gas phase, methyl isocyanide, CH 3 NC, is an efficient nucleophilic reagent toward cationic substrates. [11][12][13][14][15][16][17][18][19] This is the result of its high ionization energy (11.24 eV) and its relatively low proton affinity (839 kJ mol -1 ), 20 which prevent charge and proton exchange processes, respectively. Moreover, the high dipole moment of CH 3 NC (3.85 D) 21 favors its association with charged species and consequently increases its reaction efficiency.…”
Section: Introductionmentioning
confidence: 99%